Effects of dark-adaptation time, irradiation time and nutrient level on Fv/Fm in Prorocentrum donghaiense (Dinophyceae) during different growth phases. Issue 1 (2nd January 2019) - Sun, Kai-Ming; Xin, Ming; Li, Yan; Li, Ruixiang; Tang, Xuexi; Wang, Zongling; Sun, Ping
ABSTRACT: Factors that affect maximum quantum yield values of photosystem II ( Fv /Fm ) during exponential and stationary phases were studied in Prorocentrum donghaiense at various dark-adaptation and culture irradiation times in three nutrient treatments. Dark-adaptation and culture-irradiation times were the main factors affecting changes in Fv /Fm during exponential growth. Fv /Fm in the three nutrient treatments generally decreased over time. Significant differences in Fv / Fm were not observed in the nutrient treatments. However, at the start of stationary phase, nutrient treatment and interaction between time and nutrient treatment became the main factors that affected Fv / Fm . Longer dark-adaptation and culture-irradiation times than in the exponential phase led to greater differences in Fv / Fm as a result of different nutrient treatments. Collectively, the factors affecting measurement of Fv / Fm differed in the two growth phases. We conclude that the effects of nutrients, dark-adaptation time, and culture-irradiation time, as well as the interactions between time and nutrient treatment, should be considered before determining Fv / Fm during different growth phases.